Iron-catalyzed electrochemical C–H perfluoroalkylation of arenes. Issue 45 (13th October 2015) - Khrizanforov, Mikhail; Strekalova, Sofia; Khrizanforova, Vera; Grinenko, Valeriya; Kholin, Kirill; Kadirov, Marsil; Burganov, Timur; Gubaidullin, Aidar; Gryaznova, Tatyana; Sinyashin, Oleg; Xu, Long; Vicic, David A.; et al.
Abstract : A new iron-catalyzed reaction for the coupling of perfluoroalkyl iodides with aromatic substrates is described. Abstract : A new iron-catalyzed reaction for the coupling of perfluoroalkyl iodides (RF I) with aromatic substrates is described. The perfluoroalkylated arene products are obtained in good to excellent yields in the presence of a [(bpy)Fe(ii )] catalyst (10%) electrochemically regenerated or generated from [(bpy)Fe(iii )] at room temperature. The development, scope, and preliminary mechanistic studies of these transformations are reported.